Diagnostic yield of bronchoalveolar fluid/bronchoscopy among sputum AFB and CBNAAT negative presumptive tuberculosis patients: an observational study - Dubey, Sakshi; Gaikwad, Nitin; Meshram, Shailesh; Bagrecha, Mahavir (International Journal of Research in Medical Sciences, 2021)
Background: Tuberculosis is one of the most common chronic infections globally, especially in developing countries like India and is a leading cause of morbidity and mortality. Therefore, early diagnosis, and microbiological confirmation of pulmonary TB is important to break the chain of transmission. This study was carried out to study usefulness of fiberoptic bronchoscopy in sputum smear negative and CBNAAT negative patient of presumptive tuberculosis. Methods: It was an observational study in the Department of Respiratory medicine for duration of 2 years (Sept 2018- Aug 2020) among 100 adults cases of presumptive tuberculosis whose sputum were negative on sputum AFB and CBNAAT. Cases with relative or absolute contraindication for bronchoscopy were excluded from study. Results: Mean age of study subjects was 47.31±12.29 years; M:F was 1.2:1 and 5% had past history of tuberculosis. Most common findings on chest X-ray was alveolar opacities (40%), inhomogeneous opacity (24%), cavitary lesions (20%), cystic lesion (8%) and fibrosis (6%) in different zones of lung. BAL sent for CBNAAT testing detected 15% mycobacterial TB, 2% mycobacterial TB with Rif resistance. Zn staining testing detected 10% AFB, on culture 14% showed AFB growth,4% had malignant cell findings. Diagnostic efficacy of Zn staining of BAL showed 42.86% sensitivity, 95.35% specificity, 60% PPV, 91.11% NPV and 88% diagnostic accuracy. BAL CBNAAT testing had 78.57% sensitivity, 93.02% specificity, 64.71% PPV, 96.39% NPV and 91% diagnostic accuracy. Most common complication was bronchospasm and hypoxia. Conclusions: Fiberoptic bronchoscopy is useful investigation in establishing accurate and early diagnosis of lower respiratory tract infection.